Quercetin Can Improve Spinal Cord Injury by Regulating the mTOR Signaling Pathway - Wang, Xichen; Fu, Yuke; Botchway, Benson O. A.; Zhang, Yufeng; Zhang, Yong; Jin, Tian; Liu, Xuehong (Frontiers in Neurology, 2022)
The pathogenesis of spinal cord injury (SCI) is complex. At present, there is no effective treatment for SCI, with most current interventions focused on improving the symptoms. Inflammation, apoptosis, autophagy, and oxidative stress caused by secondary SCI may instigate serious consequences in the event of SCI. The mammalian target of rapamycin (mTOR), as a key signaling molecule, participates in the regulation of inflammation, apoptosis, and autophagy in several processes associated with SCI. Quercetin can reduce the loss of myelin sheath, enhance the ability of antioxidant stress, and promote axonal regeneration. Moreover, quercetin is also a significant player in regulating the mTOR signaling pathway that improves pathological alterations following neuronal injury. Herein, we review the therapeutic effects of quercetin in SCI through its modulation of the mTOR signaling pathway and elaborate on how it can be a potential interventional agent for SCI.